Chromosome-level genome assembly and population genetic analysis of a near-threatened rosewood species (Dalbergia cultrata Pierre Graham ex Benth) provide insights into its evolutionary and cold stress responses - Huang, Ping; Li, Changhong; Lin, Furong; Liu, Yu; Zong, Yichen; Li, Bin; Zheng, Yongqi (Frontiers in Plant Science, 2023)
Dalbergia cultrata Pierre Graham ex Benth (D. cultrata) is a precious rosewood tree species that grows in the tropical and subtropical regions of Asia. In this study, we used PacBio long-reading sequencing 2 technology and Hi-C assistance to sequence and assemble the reference genome of D. cultrata. We generated 171.47 Gb PacBio long reads and 72.43 Gb Hi-C data and yielded an assembly of 10 pseudochromosomes with a total size of 690.99 Mb and Scaffold N50 of 65.76 Mb. The analysis of specific genes revealed that the triterpenoids represented by lupeol may play an important role in D. cultrata's potential medicinal value. Using the new reference genome, we analyzed the resequencing of 19 Dalbergia accessions and found that D. cultrata and D. cochinchinensis have the latest genetic relationship. Transcriptome sequencing of D. cultrata leaves grown under cold stress revealed that MYB transcription factor and E3 ubiquitin ligase may be playing an important role in the cold response of D.cultrata. Genome resources and identified genetic variation, especially those genes related to the biosynthesis of phytochemicals and cold stress response, will be helpful for the introduction, domestication, utilization, and further breeding of Dalbergia species.